TDAH, THE CHALLENGE OF THE INCLUSION (Fiep Bulletin - online, 2014)
The inclusion is a reality and put that society in general can not seal the eyes. The attendance of students with disorders Attention Deficit Hyperactivity Disorder (ADHD), requires greater attention from teachers and teaching staff. From this point of view , this article is in a survey on the need and the right guaranteed student with ADHD doing its differentiated and appropriate site evaluation so that the concentration is not impaired, the action of the educator is key to achieving the student and his knowledge . The purpose of this article is to educate the teacher that he has an obligation to respect and assist the student in their limitations, making him go in search of conquests of knowledge and encourage them to grow educationally. Having to justify the difficulty of teachers working with students with ADHD feel the need to empower them to improve the process of teaching and learning. Thus, the teacher will perform changes in pedagogical practice adapting to the particularities of the pupil using different assessment instruments.
Keywords: ADHD; Inclusion; Teacher